PERFORMANSI HUTAN RAKYAT DI KELURAHAN SELOPURO KECAMATAN BATUWARNO KABUPATEN WONOGIRI - Anen, Nengsih (Universitas Nusa Bangsa, 2017)
Management of private forest is influenced by cultural habits and local knowledge. It can be influencing the management of forest, especially for its performance. So that, the utilities of forest resources is expected to provide its productivity, sustainability,Â and efficiency. This aim of this study was to measure the level of performance in private forest management in Selepuro Village, Batuwarno Subdistrict, Wonogiri Regency, Central Java Province. This study used a survey method. The data were conducted by interviewed using a structured questionnaire to respondents. The data were analyzed using descriptive analysis. The results showed that the level of performance of private forest in Selopuro Village was high. The private forest performance is shown by high levels of private forest productivity, sustainability of private forest management, benefits of rules in the management and efficiency of private forest cost management. Therefore a high private forest performance will encourage forest management to be better.Â Keywords: Performance, Private Forest, Private Forest Management